2004
DOI: 10.1111/j.0092-5853.2004.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Food Safety Information Impact U.S. Meat Demand?

Abstract: A theoretical model of consumer response to publicized food safety information on meat demand is developed with an empirical application to U.S. meat consumption. Evidence is found for the existence of pre-committed levels of consumption, seasonal factors, time trends, and contemporaneous own- and cross-commodity food safety concerns. The average demand response to food safety concerns is small, especially in comparison to price effects, and to previous estimates of health related issues. This small average ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
200
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(218 citation statements)
references
References 39 publications
10
200
2
Order By: Relevance
“…Apart from a subject of drinking water quality, consumer response to information that has been addressed in different topics such as eco-labeling (Teisl et al [2002]), food safety concerns (Piggott and Marsh [2004]), price information on water bills (Gaudin [2006]), and different formats of water quality reports (Johnson [2003]). Generally, they find, like we do, that the public responds to information about environmental concerns.…”
Section: Literaturementioning
confidence: 99%
“…Apart from a subject of drinking water quality, consumer response to information that has been addressed in different topics such as eco-labeling (Teisl et al [2002]), food safety concerns (Piggott and Marsh [2004]), price information on water bills (Gaudin [2006]), and different formats of water quality reports (Johnson [2003]). Generally, they find, like we do, that the public responds to information about environmental concerns.…”
Section: Literaturementioning
confidence: 99%
“…For example, Piggott and Marsh (2004) used the number of media articles on different categories of meat as a proxy for consumer exposure to food safety information and as a predictor of meat demand. In other studies, consumption data have been linked to attitudinal survey data obtained from different subjects (Jensen et al 1992).…”
Section: Attitudes and Food Demandmentioning
confidence: 99%
“…One option consumers have is to reduce consumption of products they lack confidence in. Research has shown decreased consumption of meat products in relation to food safety concerns, particularly in response to food safety incidents (Burton and Young 1996;Piggott and Marsh 2004). In addition, Verbeke and Viaene (1999) found that one third of Belgian respondents showed an intention to decrease their total meat consumption in the year following the survey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we develop a model to examine livestock disease management when both the government and producers can affect disease risks. Economic studies of livestock diseases have focused on the effects of health concerns on prices (Piggott and Marsh 2004;Lloyd et al 2001) and on estimating potential economic impacts (Matthews and Buzby 2001;Matthews and Perry 2003).…”
Section: Introductionmentioning
confidence: 99%